1974
DOI: 10.6028/nbs.nsrds.48
|View full text |Cite
|
Sign up to set email alerts
|

Radiation chemistry of ethanol :

Abstract: The yields (G) for products and intermediates formed by irradiation of ethanol, in the solid, liquid and gaseous state, have been compiled and reviewed. Rates of reactions of transient ions and radicals and spectroscopic parameters, including optical and esr spectra, are also included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…For the experiments with terphenyl, pyrene, and biphenyl, in which protonations of the anion radicals were slow, ethanol was purified by distillation from CaH 2 and then from NaBH 4 . The solvent quality was judged from the solvated electron half-life; it was 2.5 and 5.5 μs in commercial and purified ethanol, respectively; the latter compares well with the literature value of 6 μs . Monodeuterated ethanol (EtOD) was distilled from NaBD 4 .…”
Section: Methodsmentioning
confidence: 56%
“…For the experiments with terphenyl, pyrene, and biphenyl, in which protonations of the anion radicals were slow, ethanol was purified by distillation from CaH 2 and then from NaBH 4 . The solvent quality was judged from the solvated electron half-life; it was 2.5 and 5.5 μs in commercial and purified ethanol, respectively; the latter compares well with the literature value of 6 μs . Monodeuterated ethanol (EtOD) was distilled from NaBD 4 .…”
Section: Methodsmentioning
confidence: 56%
“…palustre cormus after the reaction with free carbon-centered α-hydroxyethyl radicals (HERs). The main molecular products of de-aerated ethanol radiolysis are EA (CH 3 CHO) and butanediol-2,3 …”
Section: Results and Discussionmentioning
confidence: 99%
“…They are formed as a result of the disproportionation and combination reactions of α -hydroxyethyl radicals [15,16] Maiboroda et al [17] found that reactions (1) and (2) occur with approximately equal probabilities. Solvated electron, which is formed in the radiolysis of ethanol, can decrease the apparent yield of acetaldehyde because the rate constant of the reaction of solvated electron with…”
Section: Radiolysis Of Ethanol Solutionsmentioning
confidence: 99%